The Structure and Catalytic Mechanism of Sorghum bicolor Caffeoyl-CoA O-Methyltransferase. Issue 1 (25th July 2016) - Walker, Alexander M.; Sattler, Steven A.; Regner, Matt; Jones, Jeffrey P.; Ralph, John; Vermerris, Wilfred; Sattler, Scott E.; Kang, ChulHee
Abstract : The catalytic mechanism and substrate specificity of caffeoyl-CoA O-methyltransferase from Sorghum bicolor deduced from crystal structures, site-directed mutagenesis, and kinetic and thermodynamic analyses. Abstract: Caffeoyl-coenzyme A 3- O -methyltransferase (CCoAOMT) is an S -adenosyl methionine (SAM )-dependent O -methyltransferase responsible for methylation of the meta -hydroxyl group of caffeoyl-coenzyme A (CoA) on the pathway to monolignols, with their ring methoxylation status characteristic of guaiacyl or syringyl units in lignin. In order to better understand the unique class of type 2 O -methyltransferases from monocots, we have characterized CCoAOMT from sorghum ( Sorghum bicolor ; SbCCoAOMT), including the SAM binary complex crystal structure and steady-state enzyme kinetics. Key amino acid residues were validated with site-directed mutagenesis. Isothermal titration calorimetry data indicated a sequential binding mechanism for SbCCoAOMT, wherein SAM binds prior to caffeoyl-CoA, and the enzyme showed allosteric behavior with respect to it. 5-Hydroxyferuloyl-CoA was not a substrate for SbCCoAOMT. We propose a catalytic mechanism in which lysine-180 acts as a catalytic base and deprotonates the reactive hydroxyl group of caffeoyl-CoA. This deprotonation is facilitated by the coordination of the reactive hydroxyl group by Ca 2+ in the active site, lowering the pKa of the 3′-OH group. Collectively, these data give a new perspective on the catalytic mechanism of CCoAOMTs and provide a basis for the functional diversity exhibited by type 2 plant OMTs that contain a unique insertion loop (residues 208–231) conferring affinity for phenylpropanoid-CoA thioesters. The structural model of SbCCoAOMT can serve as the basis for protein engineering approaches to enhance the nutritional, agronomic, and industrially relevant properties of sorghum.